Comparison of Creatinine, Cystatin C and Combined Creatinine-Cystatin C for Renal Function Assessment in Patients with Diabetes - Umar, Saba; Sabir, Sohail; Azam, Nadeem Malik; Aamir, Muhaamad; Bibi, Afshan; Altaf, Ashfaq; Siddiqui, Faud Ahmed; Sabir, Haroon; Raja, Khalid Mehmood; Butt, Batool (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the estimated glomerular filtration rate (eGFR) assessed through the CKD-EPI equations based on creatinine, Cystatin C and creatinine-Cystatin C levels for estimating kidney function among patients with diabetes.Study Design: Cross-sectional analytical study.Duration and Place of Study: Nephrology Department, Armed Forces Institute of Urology, Rawalpindi Pakistan, from Aug 2020 to Mar 2021.Methodology: A total of 70 patients were recruited. Serum samples were collected for creatinine and Cystatin C levels and 24 hours of urine for creatinine clearance. The eGFR values were calculated using the creatinine, Cystatin C and combined creatinine-Cystatin C CKD-EPI equations and compared with 24 hours of urinary creatinine clearance.Results: A total of 22 (31.4%) patients had early stage, while 48 (68.6%) had late-stage chronic kidney disease (CKD). The highest Spearman correlation coefficient was found for eGFR CKD-EPIcr-cys (rho=0.844), followed by CKD-EPIcys (rho= 0.835) and CKD-EPIcr (rho=0.709).Conclusion: CKD-EPIcr-cys is the most accurate, recommended method of calculating eGFR.